2013
DOI: 10.3109/02770903.2012.757778
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use in Australian Children with Asthma: User’s Perspective

Abstract: This is one of the few research studies exploring the viewpoint of children with asthma about their medications in Australia. Despite investment in dissemination of professional, targeted evidence-based asthma management strategies in healthcare, there seems to be a lack of depth in terms of what parents understand about their child's asthma. Effective communication about medication usage, especially the inclusion of the child in the consultation to empower them to be involved in their own asthma care, may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Children and adolescents with asthma may experience frustration, embarrassment and low self-confidence because of their disease-related limitations. 16 41 They may also withdraw from PA because of their parents’ fear and protectiveness. 17 Participants in the present study seemed to overcome those barriers and limitations, and the parents also supported their children's independence by being absent during intervention sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents with asthma may experience frustration, embarrassment and low self-confidence because of their disease-related limitations. 16 41 They may also withdraw from PA because of their parents’ fear and protectiveness. 17 Participants in the present study seemed to overcome those barriers and limitations, and the parents also supported their children's independence by being absent during intervention sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Misunderstandings about the disease and the way that medications work are among the patient-related factors that affect treatment adherence [16,18]. In our study, 56.3% of caregivers correctly agreed that the main cause of asthma is airway inflammation (Q7), and there was a statistically significant association between knowledge about the inflammatory nature of the disease and the presence of controlled asthma (PR ¼ 1.5, 95% CI ¼ 1.2-2.0).…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects of knowledge related to asthma management, such as poor understanding of the nature of the disease, parental myths and beliefs and a lack of knowledge about main triggers, asthma treatment and medications, have been explored in previous studies [14][15][16][17][18]. Unfortunately, we were not able to identify similar studies conducted in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 87%
“…Similarly, in previous studies, it was reported that the workload of mothers increased, some mothers had to quit their jobs, they had to ignore their own needs, and the activities performed together with and the care for the spouse and healthy child(ren) were significantly reduced. [17][18][19] It was emphasized that mothers clean the house almost every day and they change bedsheets every week. Additionally, they do not know what to do, feel desperate, constantly making an effort in order to prevent their children from getting sick, sleep beside their children at night and constantly keep their eyes on their children, and always take leave from their jobs during disease periods, which affects their professional life.…”
Section: Discussionmentioning
confidence: 99%